Strengths of Good Character to Achieve Higher Social Academic Achievement for Students of English Department at STKIP PGRI Jombang - Chalimah M.Pd; Lailatus Sa'adah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2015)
Good character is important in the daily lives of individuals and families, in the workplace, in school, and in the larger community. For centuries, building and strengthening good character among children and youth have been universal goals for parenting and education. Good character is what parents look for in their children, what teachers look for in their students, what siblings look for in their brothers and sisters, and what friends look for in each other. Character is critical for lifelong optimal human development. It has become parents’ and educators’ responsibility to encourage their children or their students to implement it.            Based on the problem above, the researcher has conducted the research to know the correlation between the strengths of character and academic  achievement for students of STKIP PGRI Jombang by using correlational research  design. The instruments used are questionnaire, likert scale, and interview. The researcher has analyzed the data by using product moment formula. The significant level is 95% (α=0,05).            The finding is rxy=0,503079 and t test=2,53734. The correlation is positive which means that there is same direction between free variable and bound variable. The higher good character which the students have, the higher social academic achievement they get. Because t test (2,53734) > t table (2,093), the conclusion is there is significant correlation between good character and social academic achievement for students of STKIP PGRI Jombang